Analysis of the impact of hotel chains on the global tourism industry - Rizova, Teodora (Leadership, Society, Strategic Visions, 2021)
With the development of global hotel services markets as well as the general trends of the transnationalization of the economy lead to the expansion of international hotel chains. Hotel chains contribute to raising the level of organization of production and tourism services, creating a certain image of hotel services.Their impact on the market is strong and competitive. They are entering new tourist destinations and their network is constantly growing. This trend will continue in the future as well as strong competition between them for markets and offering innovative services.